Strategies for stable water splitting via protected photoelectrodes. (1st March 2017) - Bae, Dowon; Seger, Brian; Vesborg, Peter C. K.; Hansen, Ole; Chorkendorff, Ib
Abstract : This review provides a comprehensive overview of the key aspects of protection strategies for achieving stable solid/liquid interfaces for photoelectrodes. Abstract : Photoelectrochemical (PEC) solar-fuel conversion is a promising approach to provide clean and storable fuel ( e.g., hydrogen and methanol) directly from sunlight, water and CO2 . However, major challenges still have to be overcome before commercialization can be achieved. One of the largest barriers to overcome is to achieve a stable PEC reaction in either strongly basic or acidic electrolytes without degradation of the semiconductor photoelectrodes. In this work, we discuss fundamental aspects of protection strategies for achieving stable solid/liquid interfaces. We then analyse the charge transfer mechanism through the protection layers for both photoanodes and photocathodes. In addition, we review protection layer approaches and their stabilities for a wide variety of experimental photoelectrodes for water reduction. Finally, we discuss key aspects which should be addressed in continued work on realizing stable and practical PEC solar water splitting systems.